Analyzing the dispersion of carbon nanotubes solution for use in Portland cement concrete - Marcondes, C. G. N.; Medeiros, M. H. F. (Revista ALCONPAT, 2016)
Carbon nanotubes (CNTs) are nanometric carbon structures with cylindrical formats. For use in concretes, one of the difficulties is in its dispersion, focus this work. It used a tool known as hierarchical analysis to investigate the efficiency of the dispersion of carbon nanotubes in concrete kneading water. Were studied 12 forms of dispersions in aqueous medium containing hum Miscellaneous Chemicals. Carbon nanotubes multi-walled in powder form and Processed already dispersed in water were used. The study showed that the hierarchical analysis tool might constitute an alternative to the election of the best choice among the available options, considering the factors of influence in a systemic way.Keywords: analytical hierarchy process; concrete; carbon nanotubes.